Pedagogy in computer-based sport training - Iskandar, Yulita Hanum P (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
The central question addressed in this paper is the appropriate formal representation of learning outcomes in the motor skill domain so they can be interpreted and manipulated by computers as well as humans for the implementation of Computer-based Sport Training (CBST). Instructional design usually begins with the specification of behavioural objectives or intended learning outcomes. The field of educational psychology has long been sensitive to the desirability of establishing learning objectives for instruction. Computerprocessable learning outeomes in the motor skill domain, however, seem to have remained the silent partner of learning outcomes in both the cognitive and affective domains. This paper presents a conceptual model of learning outcomes in the motor skill domain for the implementation ofCBST. The heart of this model is to treat athlete's skill as a contextualized space of capability either actual or potential. Rowing is the sport chosen as the study domain.